Role of Social Studies Teacher Forum in Enhancing Teacher Pedagogical Competence, Professionalism, and Innovation in Social Studies Learning - Irdayani Djasman Pakiding; Elpisah Elpisah; Rego Devilla (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyse the role of the Social Studies Teacher Forum in improving pedagogical competence, teacher professionalism, and innovation in Social Studies learning at the UPT SPF SMP Negeri 4 Makassar. This study uses a qualitative approach with a descriptive design. The research subjects consisted of the principal, the head of the subject teachers’ working group, and four social studies teachers who were also members of the subject teachers’ working group. Data collection was carried out through interviews, observations, and documentation, with data analysis including data reduction, data presentation, and drawing conclusions/verification. The results showed that the teacher forum contributed to improving teachers’ pedagogical competence through understanding the material, preparing lesson plans, and evaluating learning. However, the effectiveness of the Teacher Forum depends on the active participation of teachers and school support. In addition, the Teacher Forum also plays a role in improving teachers' professional competence, especially in mastering subject matter, utilising technology, and developing continuous professionalism. Nevertheless, the active participation of teachers and school support is essential to maximise the benefits of the Teacher Forum. The Teacher Forum also encourages innovation in social studies learning, but its success is influenced by teacher involvement, school support, and student readiness. Therefore, more concrete efforts are needed to optimise the role of the teacher forum in developing innovative learning strategies.